2016
DOI: 10.1080/13651501.2016.1199811
|View full text |Cite
|
Sign up to set email alerts
|

Pathological narcissism and somatic symptoms among men and women attending an outpatient mental health clinic

Abstract: The connection between narcissistic pathology and somatic symptom severity appears to differ based on gender. Further research is needed to confirm and extend this preliminary finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A further study examining the association of vulnerable narcissism (assessed with the Hypersensitive Narcissism Scale, HSNS: [31]) and depression severity (BDI) in dysthymic outpatients supported a significant positive association between the two constructs [32]. Differently, in mixed samples of psychiatric outpatients [33,34], positive but non-significant direct associations were revealed between narcissistic vulnerability and grandiosity (PNI) and depressive symptom severity (Patient Health Questionnaire, PHQ-9; [35]).…”
Section: Narcissism and Depressionmentioning
confidence: 90%
“…A further study examining the association of vulnerable narcissism (assessed with the Hypersensitive Narcissism Scale, HSNS: [31]) and depression severity (BDI) in dysthymic outpatients supported a significant positive association between the two constructs [32]. Differently, in mixed samples of psychiatric outpatients [33,34], positive but non-significant direct associations were revealed between narcissistic vulnerability and grandiosity (PNI) and depressive symptom severity (Patient Health Questionnaire, PHQ-9; [35]).…”
Section: Narcissism and Depressionmentioning
confidence: 90%
“…Such data may allow for the delineation of specific symptoms which impact on the presentation of narcissism in males and females, and thus may require gender-sensitive interventions that address such indicators. Future research should also explore gender differences in patients with narcissistic pathology to evaluate whether expressions of narcissism shift depending on the severity of dysfunction ( Kealy et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study also demonstrated a connection between pathological narcissism and hypersensitivity, which is also an interesting finding in the context of chronic pain. 29 In clinical pain therapy, challenges coming along with individual personalities and especially with PD have not been systematically incorporated yet. Particularly, in the context of interdisciplinary treatment programmes, once the indication for an interdisciplinary treatment is set, all patients go through the same programme.…”
Section: Discussionmentioning
confidence: 99%